The Effectiveness of Using Journals to Enhance Students' Confidence in Their Psychological Ability to Master the Arabic Language - Mudea Dwi Anugrah; Ahmad Royani; Erta Mahyudin (Al-Muyassar: Journal of Arabic Education, 2025)
This research is based on the importance of mastering Arabic as a key competency for students at Madrasah Tsanawiyah Islamiyah Ciputat. However, in reality, many students lack confidence in their ability to learn and master the Arabic language. This issue is evident at the research site, where students tend to hesitate in demonstrating their skills in various aspects of Arabic, such as vocabulary (mufradat), syntax (tarkib), and reading comprehension (qira’ah). This study aims to examine the effectiveness of using daily journals in enhancing students  confidence in Arabic language proficiency and to determine the improvement in students' learning outcomes before and after implementing this method. The study employs a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consists of 61 ninth-grade students divided into two groups: 24 students in the experimental class, who used daily journals, and 37 students in the control class, who followed traditional methods. Both groups were assessed using pre-tests and post-tests. Data were collected through tests, observations, and interviews. The findings indicate that daily journals effectively enhance students' confidence. The experimental group's average post-test score was 80.20, compared to 59.27 in the control group. The t-test results show a significance value of 0.226 (>0.05), indicating significant improvement. The N-Gain score of 0.4 categorizes the method as moderately effective. Thus, daily journals not only boost students' confidence but also improve their Arabic proficiency. Keywords: Effectiveness, Daily Journal, Confidence, Arabic Language Proficiency. مستخلص البحثيستند هذا البحث إلى أهمية إجادة اللغة العربية كإحدى الك?اءات الأساسية التي يجب أن يمتلكها طلاب المدرسة الإسلامية المتوسطة تشيبوتات. ومع ذلك، ?إن الواقع يشير إلى أن العديد من الطلاب ي?تقرون إلى الثقة بأن?سهم ?ي تعلم اللغة العربية وإتقانها. وقد لوحظ ذلك ?ي موقع البحث، حيث يميل الطلاب إلى التردد ?ي إظهار قدراتهم. يهد? هذا البحث إلى الكش? عن ?عالية استخدام اليوميات لترقية ثقة التلاميذ بأن?سهم على إجادة اللغة العربية، بالإضا?ة إلى معر?ة تحسين نتائج تعلمهم قبل وبعد تطبيق هذا الأسلوب. استخدم هذا البحث منهجًا كميًا بأسلوب شبه تجريبي (تصميم المجموعة الضابطة غير المتكا?ئة). تأل?ت عينة البحث من ٦١ طالبًا من الص? التاسع، تم تقسيمهم إلى مجموعتين: ٢٤ طالبًا ?ي المجموعة التجريبية الذين استخدموا اليوميات و٣٧ طالبًا ?ي المجموعة الضابطة الذين استخدموا الأسلوب التقليدي. تم تقييم كلتا المجموعتين باستخدام اختبار قبلي واختبار بعدي. ج?معت البيانات من خلال الاختبارات، الملاحظة، والمقابلات. أظهرت نتائج البحث أن استخدام اليوميات كان ?عالًا ?ي ترقية ثقة التلاميذ بأن?سهم. وقد أثبتت النتائج ذلك من خلال متوسط درجات الاختبار البعدي للمجموعة التجريبية الذي بلغ ٨٠.٢٠ مقارنة بالمجموعة الضابطة التي بلغ متوسطها ٥٩.٢٧. وأظهر اختبار "تي" أن قيمة الدلالة بلغت ٠.٢٢٦، وهي أكبر من ٠.٠٥، مما يعني ر?ض ال?رضية الص?رية (Ho) وقبول ال?رضية البديلة (Ha)، وبالتالي يمكن الاستنتاج أن هناك تحسنًا ملحوظًا ?ي ثقة التلاميذ بأن?سهم بعد استخدام اليوميات. بالإضا?ة إلى ذلك، أظهرت نتيجة اختبار N-Gain أن ?عالية الأسلوب كانت عند مستوى متوسط بقيمة بلغت ٠.٤. الكلمات الم?تاحية: ?عالية، اليوميات، الثقة بالن?س، إجادة اللغة العربية.